EFFECT OF POTASSIUM NUTRITION ON POTATO YIELD, QUALITY AND NUTRIENT USE EFFICIENCY UNDER VARIED LEVELS OF NITROGEN APPLICATION - Singh, S K; Lal, S S (Potato Journal, 2013)
A field trail was conducted during winter season of 2009-10 and 2010-11 at Central Potato Research station, Patna on sandy loam soil under irrigated condition to find suitable dose of potassium for potato cultivar Kufri Pukhraj for optimum yield, quality and nutrient use efficiency under different nitrogen levels. There was significant positive interaction between N and K. At each level of N, increasing levels of K application increased the tuber yield, N and K uptake by potato at harvest. Potassium and N application improved tuber size by increasing the large and medium grade yield and decreasing the small and very small sized tuber. Maximum yield of 39.83 t /ha was obtained when N and K was applied @ 225 kg/ ha and 150 kg K2O/ ha against a tuber yield of only 14.36 t/ ha without N and K application. The recovery efficiencies of K and N fertilizer on potato increased at 100 kg K2O and 150 kg N/ ha. There was less weight loss and rottage of tubers with potassium application whereas with increase in nitrogen levels there was increase in weight loss due to tuber rottage.